NATO Burden Sharing after the Wales Summit: A Generalized Set Qualitative Analysis. Issue 6 (18th August 2022) - Haesebrouck, Tim
ABSTRACT: At the 2014 Wales Summit, the NATO allies pledged to spend at least 2% of their GDP on defence by 2024. While some allies are on track to meet the 2% target, others only modestly augmented their military expenditures and still others have even reduced their defence budgets. This article aims to explain the diverging trajectories of the allies' military expenditures during the first five years after the Wales Summit. More specifically, it introduces an integrated burden sharing model, which is tested with generalized set Qualitative Comparative Analysis. The results of the analysis indicate that the threat posed by Russia provided the most important incentive for increasing defence budgets. However, general budget constraints kept some allies from increasing their defence budget in proportion to the threat posed by Russia. Conversely, in the absence of budget constraints, allies governed by a right-leaning executive made intermediate budget efforts even if they only faced a low level of threat. Strikingly, budget inertia only had a modest impact on the allies' defence budgets, only resulting in a low level of spending in allies that were not threatened by Russia and either faced considerable budget constraints or were governed by a left-wing government.